2008
DOI: 10.1007/s00701-008-1618-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of monocyte chemoattractant protein-1 in patients experiencing neurocognitive decline following carotid endarterectomy

Abstract: SummaryBackground-Previous studies have demonstrated that elevated pre-operative monocyte count is an independent predictor of acute neurocognitive decline following carotid endarterectomy (CEA). Monocyte chemoattractant protein-1 (MCP-1), secreted by human endothelial and monocyte-like cells, is a potent mediator of inflammation and mononuclear cell trafficking. This study examines the relationship between peri-operative serum MCP-1 elevation and post-operative neurocognitive injury following CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Endothelial cells, macrophage-like cells, and neurons all express MCP-1 in the ischemic brain. Animal models studies suggest that MCP-1 contributes to exaggerate responses to ischaemia/reperfusion injury, and immunoneutralization of MCP-1 results in decreased infarct size (Mack et al 2008). Furthermore, elevated MCP-1 protein levels have been demonstrated in human cerebrospinal fluid 24 h after stroke.…”
Section: Discussionmentioning
confidence: 95%
“…Endothelial cells, macrophage-like cells, and neurons all express MCP-1 in the ischemic brain. Animal models studies suggest that MCP-1 contributes to exaggerate responses to ischaemia/reperfusion injury, and immunoneutralization of MCP-1 results in decreased infarct size (Mack et al 2008). Furthermore, elevated MCP-1 protein levels have been demonstrated in human cerebrospinal fluid 24 h after stroke.…”
Section: Discussionmentioning
confidence: 95%
“…MCP-1 has also been shown to attract monocytes to the brain during stress and has exhibited increased expression in the brains of suicide victims (Torres-Platas et al, 2014). Although no study has reported a significant relationship between MCP-1 and psychomotor slowing, it has been associated with cognitive impairment in multiple clinical populations including first episode psychosis (Martinez-Cengotitabengoa et al, 2012), mild cognitive impairment and early stage Alzheimer’s Disease (Galimberti et al, 2006; Westin et al, 2012), HIV-associated cognitive deficits (Yuan et al, 2015), and neurocognitive deficits post carotid endarterectomy (Mack et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Because the incidence of perioperative stroke is exceedingly rare, investigators are studying subtler forms of neurological injury, such as eCD, to increase the neurological safety of this commonly performed procedure. A number of studies have attempted to elucidate the underlying pathophysiology of this eCD, 3,12,13,18,20,21,31 because it is exhibited by approximately 25% of patients after CEA. This is the first study to evaluate the adequacy of cerebral collateral circulation as a predictor of eCD after CEA.…”
Section: Discussionmentioning
confidence: 99%
“…All CEA procedures were performed under general anesthesia with routine monitoring as well as continuous electroencephalographic monitoring to detect cerebral ischemia, as previously described. 3,12,13,18,20,21,31 An intraoperative CA shunt was placed in 4 patients with significant electroencephalographic changes consistent with cerebral ischemia, and these patients were subsequently excluded from this study. The remaining 38 patients were included in the statistical analysis.…”
Section: Study Subjectsmentioning
confidence: 99%